1985
DOI: 10.1901/jaba.1985.18-303
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Self‐initiated Toileting in Infants

Abstract: We evaluated a method for training infants to cue their mothers on the need to eliminate. The program consisted of three phases: Phase I was directed at establishing a close temporal relationship between body signals (straining) and subsequent defecations on the potty; Phase II was designed to establish a relationship between prompted and unprompted potty reaching/grabbing responses and eliminations (defecations and urinations) on the potty; and Phase III served to establish unprompted potty reaching/grabbing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
11

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 3 publications
1
21
0
11
Order By: Relevance
“…One Vietnamese paper showed that infants can be trained by 1 year old, and that the postvoid residual urine volume decreased after infant TT [31] . Although the experience of the Digo people of Kenya is the most referenced paper [13] , the same ‘parent-centred’ technique was successfully applied in the Netherlands with 3–7-month-old infants [32] .…”
Section: Resultsmentioning
confidence: 99%
“…One Vietnamese paper showed that infants can be trained by 1 year old, and that the postvoid residual urine volume decreased after infant TT [31] . Although the experience of the Digo people of Kenya is the most referenced paper [13] , the same ‘parent-centred’ technique was successfully applied in the Netherlands with 3–7-month-old infants [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Over time, previous criterion responses are no longer sufficient for reinforcement and undergo extinction as closer approximations to the target response are reinforced (cf. Athens, Vollmer, & St. Peter Pipkin, 2007;Galbicka, 1994;Platt, 1973;Smeets, Lancioni, Ball, & Oliva, 1985).…”
Section: Extinction Of Schedule-maintained Respondingmentioning
confidence: 99%
“…All three of her sons, including one with Down syndrome, achieved bowel and bladder control before they could walk. This report inspired a later controlled prospective investigation that yielded identical results with all four infants studied [9]. In a pioneering cross-cultural investigation of traditional toilet training practices among the East African Digo tribe, deVries and deVries found training success occurred at approximately 4-6 months of age [4].…”
mentioning
confidence: 68%